Cotton Leaf Curl Multan virus C4 protein suppresses both transcriptional and post-transcriptional gene silencing by interacting with SAM synthetase - Ismayil, Asigul (PLoS Pathog, 2018)
Gene silencing is a natural antiviral defense mechanism in plants. For effective infection, plant viruses encode viral silencing suppressors to counter this plant antiviral response. The geminivirus-encoded C4 protein has been identified as a gene silencing suppressor, but the underlying mechanism of action has not been characterized. Here, we report that Cotton Leaf Curl Multan virus (CLCuMuV) C4 protein interacts with S-adenosyl methionine synthetase (SAMS), a core enzyme in the methyl cycle, and inhibits SAMS enzymatic activity. By contrast, an R13A mutation in C4 abolished its capacity to interact with SAMS and to suppress SAMS enzymatic activity. Overexpression of wild-type C4, but not mutant C4(R13A), suppresses both transcriptional gene silencing (TGS) and post-transcriptional gene silencing (PTGS). Plants infected with CLCuMuV carrying C4(R13A) show decreased levels of symptoms and viral DNA accumulation associated with enhanced viral DNA methylation. Furthermore, silencing of NbSAMS2 reduces both TGS and PTGS, but enhanced plant susceptibility to two geminiviruses CLCuMuV and Tomato yellow leaf curl China virus. These data suggest that CLCuMuV C4 suppresses both TGS and PTGS by inhibiting SAMS activity to enhance CLCuMuV infection in plants.